Race based inequalities for Indigenous Australians' participation and engagement in VET: a targeted review of the research. (3rd July 2017) - Cameron, Roslyn; Stuart, Lynne; Bell, Terry
Abstract: The poor outcomes in education, training and employment achieved by Aboriginal and Torres Strait Islander people in Australia have been well documented. The transition from a traditional Indigenous society to the statuses of mainstream Australian society has been, and continues to be problematic for Indigenous Australians. The participation in vocational education and training (VET) and employment outcomes for Indigenous Australians has been historically much lower than for non-Indigenous Australians. The aim of this paper is to undertake a targeted review of the existing literature and research into the participation and engagement of Indigenous Australians in VET through a content analysis of three VET based journals, nationally funded VET research and a VET database. The findings point to the publishing of very little research in academic journals however research funded through the National Centre for Vocational Education Research appears to be a prime source of published grey literature. The paper proceeds to discuss the findings in the light of a proposed future research agenda.